The impact of risk management processes on clinical negligence claims across NHS acute hospital trusts - Egan, Tom (2012)
The pursuit of healthcare quality is a global trend as countries attempt to maximise the usage of resources amidst concerns about increasing costs and patient safety. The incentives for high quality care were traditionally provided by the tort system of medical negligence; however, modifications to this system saw it replaced in the UK in 1990 with a fault-based enterprise liability system (NHS Indemnity) - NHS trusts were now indemnified for clinical negligence claims in return for the payment of insurance premiums to the NHSLA which assumed responsibility for claims management. The incentives for quality care in this system evolved to a system of risk management standards in the 2002-2009 period – such standards offered reputational and financial benefits to trusts who achieved higher risk management levels (the attainment of such higher levels is proposed to be dependent on the trust governance structure and financial health), and the impact of this system on the clinical negligence outcomes of NHS trusts is the particular focus of this study. A lack of suitable data restricted previous studies of the effectiveness of risk management standards; however, the availability of such data permitted an empirical analysis of a unique panel database. This analysis initially found that the adoption of a new governance structure (i.e. foundation trust) is significantly associated with higher risk management levels, while efficient risk management processes are found to be significantly associated with lower numbers of clinical negligence claims. Finally, foundation trusts were found to be associated with higher closed claim values i.e. such trusts are willing to offer higher amounts to settle claims early. Overall, this study supports the proposition that more efficient risk management processes will lead to improved clinical negligence outcomes for NHS trusts, and recommendations are offered to assist trusts to become more efficient at risk management.